Assessment of natural cellulosic powder from pepper pericarp waste (Piper nigrum L.) after alkalization and bleaching treatment : effect of alkali concentration and treatment cycle - Ain Nadiah Sofiah Ahmad Khorairi; Noor-Soffalina Sofian-Seng; Rizafizah Othaman; Noorul Syuhada Mohd Razali; Khairul Farihan Kasim (Penerbit Universiti Kebangsaan Malaysia, 2022)
Pepper (Piper nigrum L.) pericarp is an agriculture waste in the production of white pepper. It is underutilised agro-industrial waste which could be a promising natural source of cellulose. Hence, finding an optimum way to remove the non cellulose components without degrading the cellulose structure is essential. In this work, the effects of alkaline concentration (4, 5, and 6% NaOH) and number of soaking cycle (3 & 4 cycles) on the characteristics of cellulose from pepper pericarp were investigated. The obtained cellulose powder was characterized for its yield, α-cellulose content, particle size, zeta potential, morphology, whiteness index, crystallinity degree and thermal stability. The white powder cellulose after 4th cycle treatment with 4% NaOH appeared to have the highest yield (23.63%), α-cellulose (65.97%), crystallinity structure (51%) and better thermal stability at 334 °C. FTIR spectrum at band around 1732 cm-1 indicates a partial removal of non-cellulosic material at all alkalization condition due to the presence of remaining lignin and hemicellulose. These may contribute to formation of negative surface charge on all cellulose samples which may potentially enhance the functionality of the material as emulsifier. Based on two-way ANOVA test, concentration and cycle of alkaline treatment significantly (p<0.05) influenced the yield, particle size and zeta potential, meanwhile α-cellulose significantly influence by NaOH concentration only (p<0.05). The findings showed that manipulating the synthesis condition of cellulose powder influenced its properties which could be further used in various applications.